PROTOCOLO COM INTERVENÇÃO PARA REABILITAÇÃO DE INFANTES ÓRFÃOS DE PREGUIÇA-DE-GARGANTA-MARROM Bradypus variegatus Schinz, 1825 (PILOSA: BRADYPODIDAE) - Lira, Viviane César de; Xavier, Gileno Antônio Araújo; Valença, Yuri Marinho; Barros e Silva, Tatiane Clericuzi de (Revista Nordestina de Zoologia, 2026)
After a gestation period of approximately six months, the species Bradypus variegatus abandons its offspring, initiating a process known as social weaning. The mother leaves the area where the juvenile was raised and relocates to another part of the forest. In the wild, for various reasons, some young sloths may become orphaned. Although they may have acquired limited learning from their mothers, when rescued and kept in captivity, they require rehabilitation in Wildlife Screening Centers. This study aimed to develop a rehabilitation protocol for orphaned B. variegatus juveniles at CETRAS Tangará, Recife, Pernambuco. A selection of non-sexed infant individuals was kept in an enriched enclosure with tree trunks and branches. Behavioural observations and interventions related to locomotion, feeding, and defense activities were recorded using Focal and Scan sampling methods. Locomotor enrichment involved replacing branches with varying thicknesses and heights. For feeding enrichment, leaves from Artocarpus heterophyllus, Ficus sp., and Inga sp. species were provided. Defensive enrichment consisted of exposing the animals to caged predators near the enclosure (a spectacled owl Pulsatrix perspicillata, a southern caracara Caracara plancus, and a jaguarundi Herpailurus yagouaroundi). Following these interventions, an ethogram was developed to document the behaviors displayed. A significant increase in behavioral expressions was observed during the intervention phase, followed by a reduction in the post-intervention phase. The results demonstrate that the interventions effectively stimulated naturalistic behaviors and increased activity levels. The study highlights the positive impact of such interventions on rehabilitation, resulting in a more diverse and age-appropriate behavioral repertoire. It underscores the need to improve rehabilitation practices, protocols, and post-release monitoring to minimize risks and enhance the species’ chances of survival in the wild.